2021
DOI: 10.3390/insects12060497
|View full text |Cite
|
Sign up to set email alerts
|

Can Plant Lectins Help to Elucidate Insect Lectin-Mediated Immune Response?

Abstract: Lectins are carbohydrate-binding proteins that recognize and selectively bind to specific sugar structures. This group of proteins is widespread in plants, animals, and microorganisms, and exerts a broad range of functions. Many plant lectins were identified as exogenous stimuli of vertebrate immunity. Despite being the largest and most diverse taxon on earth, the study of lectins and their functions in insects is lagging behind. In insects, research on lectins and their biological importance has mainly focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 149 publications
(175 reference statements)
0
4
0
Order By: Relevance
“…These effects resemble to the immune effect of encapsulation, a process in which hemocytes gather together and enclose a pathogen by making a capsule‐like structure, thereby limiting its mobility, development and/or proliferation (Ishihara et al ., 2017), suggesting this lectin might have immunomodulatory effects on insect cells. The immunomodulatory activity of plant lectins is often associated with their interaction with glycan moieties present on cell surfaces (reviewed by Chen et al ., 2021). Such interactions can result in a signal transduction, which triggers the effector mechanisms involved in the immune response (reviewed by Souza et al ., 2013; Chen et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects resemble to the immune effect of encapsulation, a process in which hemocytes gather together and enclose a pathogen by making a capsule‐like structure, thereby limiting its mobility, development and/or proliferation (Ishihara et al ., 2017), suggesting this lectin might have immunomodulatory effects on insect cells. The immunomodulatory activity of plant lectins is often associated with their interaction with glycan moieties present on cell surfaces (reviewed by Chen et al ., 2021). Such interactions can result in a signal transduction, which triggers the effector mechanisms involved in the immune response (reviewed by Souza et al ., 2013; Chen et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The immunomodulatory activity of plant lectins is often associated with their interaction with glycan moieties present on cell surfaces (reviewed by Chen et al ., 2021). Such interactions can result in a signal transduction, which triggers the effector mechanisms involved in the immune response (reviewed by Souza et al ., 2013; Chen et al ., 2021). In this study, Orysata was observed to readily bind to the cell surface of D. melanogaster S2 cells, possibly through interaction with the glycans of the glycoproteins on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…In such strategies, carbohydrate binding proteins, or lectins, with a specificity for fucosylated glycans, e.g., F-type lectins (Vasta et al 2017, Vasta & Feng 2020) could be used to disrupt the insect immune response against parasitoids or fungal or microbial agents. The role of lectins in the insect immune system have recently been summarized (Chen et al 2021, Ming et al 2023. In addition to the model D. melanogaster, the study of honeybees is gaining more attention as its royal jelly is a natural antimicrobial agent (Fratini et al 2016), while its venom is allergenic (Pucca et al 2019).…”
Section: In Insectsmentioning
confidence: 99%
“…Lectins are proteins found naturally in most plants; they enhance plant immunity during plant-insect interactions through the release of cytokines and other effectors. However, the mechanism of plant lectin production in response to insect or pathogen attacks remains unclear [142].…”
Section: Smsmentioning
confidence: 99%